2018
DOI: 10.1080/1354750x.2018.1488275
|View full text |Cite
|
Sign up to set email alerts
|

Identification of candidate microRNA biomarkers in renal fibrosis: a meta-analysis of profiling studies

Abstract: The prognostic, diagnostic and therapeutic value of microRNA (miRNA) expression aberrations in renal fibrosis has been studied in recent years. However, the miRNA expression profiling efforts have led to inconsistent results between the studies. The aim of this study was to perform a meta-analysis on the renal fibrosis miRNA expression profiling studies to identify candidate diagnostic biomarkers. We performed comprehensive literature searches in several databases to identify miRNA expression studies of renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 64 publications
4
26
0
Order By: Relevance
“…In the downregulated network, miR-181a, miR-181b, miR-181c and miR-181d were predicted to regulate Mat2a, Timp3 and Igsf11. Among these miRNAs, miR-142-5p was identified as a candidate biomarker of renal fibrosis [38]. miR-181a was documented to mediate cell apoptosis in cisplatin-treated HK-2 cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…In the downregulated network, miR-181a, miR-181b, miR-181c and miR-181d were predicted to regulate Mat2a, Timp3 and Igsf11. Among these miRNAs, miR-142-5p was identified as a candidate biomarker of renal fibrosis [38]. miR-181a was documented to mediate cell apoptosis in cisplatin-treated HK-2 cells [39].…”
Section: Discussionmentioning
confidence: 99%
“…Exosomes in urine are reliable tool for the analysis of miRNAs in kidney diseases, since many miRNAs originated from the kidney cells [ 87 ]. The expression of various miRNAs are dysregulated in different kidney conditions, for instance, the aberrations of miRNA expression in kidney fibrosis was described in a recent meta-analysis, identifying five upregulated (miR-142–3p, miR-223–3p, miR-21–5p, miR-142–5p, miR-214–3p) and two downregulated (miR-29c-3p, miR-200a-3p) miRNAs [ 120 ].…”
Section: Modality Of Mirna Testingmentioning
confidence: 99%
“…Gu et al conducted a miRNAs study using hypertensive rats, and found that chronic aerobic exercise training improved RAAS balance, decreased blood pressure by down-regulation of the expression of miR-143. The result was accompanied by significantly elevated circulating ACE2 and angiotensin (1–7) levels [ 120 , 121 ]. Another study conducted by Lambert et al showed that miR-421 (located on chromosome X q13.2) could decrease the ACE2 protein expression by translational repression [ 128 , 137 , 21 ].…”
Section: Modality Of Mirna Testingmentioning
confidence: 99%
See 1 more Smart Citation
“…In any case, a recent review about miRNA in patients with diabetic kidney disease identified miR-21-5p, miR-29a-3p, miR-126-3p, miR-192-5p, miR-214-3p, and miR-342-3p that are consistently dysregulated among different studies, and bioinformatics analysis revealed that all of them play essential roles in diabetic kidney disease. Finally, a recent meta-analysis from 20 datasets from human and animal studies is aimed at recognizing consistently dysregulated miRNAs in renal fibrosis and identifying 5 upregulated and 2 downregulated miRNA [166]. Thus, miR-1423p, miR-2233p, miR-215p, miR-1425p, and miR-2143p were shown to be consistently upregulated in several reports, whereas miR-29c-3p and miR-200a-3p were downregulated.…”
Section: Introductionmentioning
confidence: 99%